Sequence Variation in Toxoplasma gondii rop17 Gene among Strains from Different Hosts and Geographical Locations - Nian-Zhang Zhang; Ying Xu; Si-Yang Huang; Dong-Hui Zhou; Rui-Ai Wang; Xing-Quan Zhu (The Scientific World Journal)
Genetic diversity of T. gondii is a concern of many studies, due to the biological and epidemiological diversity of this parasite. The present study examined sequence variation in rhoptry protein 17 (ROP17) gene among T. gondii isolates from different hosts and geographical regions. The rop17 gene was amplified and sequenced from 10 T. gondii strains, and phylogenetic relationship among these T. gondii strains was reconstructed using maximum parsimony (MP), neighbor-joining (NJ), and maximum likelihood (ML) analyses. The partial rop17 gene sequences were 1375 bp in length and A+T contents varied from 49.45% to 50.11% among all examined T. gondii strains. Sequence analysis identified 33 variable nucleotide positions (2.1%), 16 of which were identified as transitions. Phylogeny reconstruction based on rop17 gene data revealed two major clusters which could readily distinguish Type I and Type II strains. Analyses of sequence variations in nucleotides and amino acids among these strains revealed high ratio of nonsynonymous to synonymous polymorphisms (>1), indicating that rop17 shows signs of positive selection. This study demonstrated the existence of slightly high sequence variability in the rop17 gene sequences among T. gondii strains from different hosts and geographical regions, suggesting that rop17 gene may represent a new genetic marker for population genetic studies of T. gondii isolates.